Neonatal perforated appendicitis in incarcerated inguinal hernia in the differential diagnosis of testis torsion. Issue 7 (26th July 2017) - Erginel, Basak; Soysal, Feryal Gun; Celik, Alaaddin; Salman, Tansu
Abstract: Appendicitis in newborns is uncommon and difficult to diagnose. Reports on neonatal appendicitis subsequent to inguinal hernia incarceration are exceptionally rare. We present the case of a 26‐day‐old infant with perforated appendicitis due to incarceration of a right inguinal hernia, mimicking right testicular torsion.